The dynamics of consumer behavior and the transition to sustainable consumption patterns - Ulrich Witt (Max Planck Institute of Economics, 2011)
Strong growth in disposable income has driven, and is still driving, consumption to unprecedented, but not sustainable levels. To explain the dynamic interplay of needs, need satisfaction, and innovation underlying that growth a behavioral theory of consumption is suggested and discussed with respect to its implications for making a transition to more sustainable patterns of consumer behavior.
urn:nbn:de:gbv:27-20110630-113735-2
Keywords: A13; B52; D01; D03; D11; Q50; Q56; 330; consumption; growth; sustainability; satiation; innovation; welfare; Konsumentenverhalten; Wirtschaftswachstum; Bedürfnisse; Innovation; Nachhaltige Entwicklung; Theorie